Usaha- Usaha Swalayan R & B Untuk Mempertahankan Loyalitas Pelanggannya Pasca Pandemi COVID-19 - Liling Lenlioni; Rohaetin, Sri; Windy Utami Putri; Sundari, Sundari; Alexandro, Rinto; Ayu Asfira (FKIP, Universitas Palangka Raya, 2024)
This research aims to describe the efforts of R&B Supermarkets in maintaining customer loyalty after Covid 19. The approach used is a qualitative approach with the research subjects being the owners and employees of R&B Supermarkets located in Muara Teweh Regency, Central Kalimantan. Data collection was carried out through interviews, observation and documentation. Data analysis includes data reduction, data presentation and drawing conclusions. The research results show that R&B Self-Service still exists and is able to survive amidst competition for customers after the Covid-19 pandemic. The strategy implemented by Swalayan R&B to maintain customer loyalty after Covid 19 is the best service and a friendly, pleasant and satisfying attitude towards consumers, guaranteed quality of goods, affordable prices, and flexibility in payments both cash and non-cash. It is hoped that the results of this research will be useful as a scientific reference that can be conveyed to students as intellectuals and prospective young entrepreneurs as drivers of the economy in the future